2014
DOI: 10.1021/ic501018a
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Pathways Open to Copper Water Oxidation Catalysts Containing Proximal Hydroxy Groups During Basic Electrocatalysis

Abstract: Water oxidation can lead to a sustainable source of energy, but for water oxidation catalysts to be economical they must use earth abundant metals. We report here 2:1 6,6'-dihydroxybipyridine (6,6'-dhbp)/copper complexes that are capable of electrocatalytic water oxidation in aqueous base (pH = 10-14). Two crystal structures of the complex that contains 6,6'-dhbp and copper(II) in a ratio of 2:1 (complex 1) are presented at different protonation states. The thermodynamic acid dissociation constants were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 42 publications
3
118
0
Order By: Relevance
“…It is expected that the two protons of each respective deprotonation event are lost by different ligands, to more evenly distribute the negative charge throughout the molecule. Additionally, a structure solved by Papish and co-workers with two coordinated 6,6 0 -dihydroxy-2,2 0 -bipyridine ligands to Cu II shows this effect with one proton removed from each ligand [23]. A similar effect is seen in the structure of 1 with the symmetry regarding protonation states of the two bpy(OH) 2 ligands.…”
Section: Absorbance Spectroscopymentioning
confidence: 72%
See 1 more Smart Citation
“…It is expected that the two protons of each respective deprotonation event are lost by different ligands, to more evenly distribute the negative charge throughout the molecule. Additionally, a structure solved by Papish and co-workers with two coordinated 6,6 0 -dihydroxy-2,2 0 -bipyridine ligands to Cu II shows this effect with one proton removed from each ligand [23]. A similar effect is seen in the structure of 1 with the symmetry regarding protonation states of the two bpy(OH) 2 ligands.…”
Section: Absorbance Spectroscopymentioning
confidence: 72%
“…These catalysts have gained attention for their facilitated electron transfer when compared to neutral ligands with respect to high-valent intermediates. Some catalysts have been designed that utilize similar principles to tune their reactivity through pH dependent catalysis, which could provide a useful control mechanism [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Following the report by Mayer et al, several attempts to lower the overpotential of copper-based catalysts were reported. Lin et al 33 and Papish et al 34 independently developed a system using 6,6¤-dihydroxy-2,2¤-bipyridine (6,6¤-dhbpy), which could facilitate PCET events, as a ligand. In the report by the Lin group, the electrochemical properties of a basic aqueous solution containing a Cu(II) salt and 6,6¤-dhbpy were investigated, and water oxidation with a low overpotential (© = 510560 mV at pH 1214) was confirmed.…”
Section: Copper-based Water Oxidation Catalystsmentioning
confidence: 99%
“…Due to substantial faster ligand dissociation kinetics at these first row transitions metals, control over the catalyst structure is considerably more cumbersome. Nevertheless, molecular catalysts in case of manganese [17], iron [18][19][20], cobalt [21] and since very recently copper [22][23][24][25][26][27][28][29][30] have been reported. Especially in case of the latter, lig- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…A fruitful strategy to prevent formation of copper oxides appears to lie with multi-denticity [29]. Nevertheless, also the copper bipyridine complexes, first reported by Mayer et al, appear to react exclusively via molecular sites [22,23], suggesting that discrimination between homogeneous versus heterogeneous catalysis is much more complex. From early cobalt polyoxometallate water oxidation chemistry the scientific community has already learned that the formation of which type of catalytic species is formed can be largely dependent on the exact reaction conditions applied, especially in case of highly dynamic systems [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%